2008
DOI: 10.1128/cvi.00065-08
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spaceflight on Ability of Monocytes To Respond to Endotoxins of Gram-Negative Bacteria

Abstract: Astronauts live and work in relatively crowded, confined environments on the Space Shuttle and the International Space Station. They experience a unique set of stressors that contribute to a diminishment of many immune responses. This study investigated the ability of the shuttle crew members' monocytes to respond to gram-negative endotoxin that they could encounter during infections. Blood specimens were collected from 20 crew members and 15 control subjects 10 days before launch, 3 to 4 h after landing, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 39 publications
(44 reference statements)
2
60
0
Order By: Relevance
“…Such alterations in immune function are similar to those brought about when there is increased immune activation produced by exposure to pathogen associated molecular patterns (PAMPs), such as LPS (161166). Specific examples of this are as follows: a reduction in proinflammatory cytokine production by myeloid cells (166, 167), a reduction in antigen-specific T cell effector cytokine responses (161) and a reduction in circulating NK cells (168). The changes in responses brought about by exposure to PAMPs are known as “tolerance”, in which subsequent responses are reduced in quality and quantity, which is thought to protect the host by limiting excessive inflammation and preventing septic shock (166, 169).…”
Section: Acute Radiation Effectsmentioning
confidence: 99%
“…Such alterations in immune function are similar to those brought about when there is increased immune activation produced by exposure to pathogen associated molecular patterns (PAMPs), such as LPS (161166). Specific examples of this are as follows: a reduction in proinflammatory cytokine production by myeloid cells (166, 167), a reduction in antigen-specific T cell effector cytokine responses (161) and a reduction in circulating NK cells (168). The changes in responses brought about by exposure to PAMPs are known as “tolerance”, in which subsequent responses are reduced in quality and quantity, which is thought to protect the host by limiting excessive inflammation and preventing septic shock (166, 169).…”
Section: Acute Radiation Effectsmentioning
confidence: 99%
“…Parabolic flight induces an increase in PMN number and the capability of PMNs to produce hydrogen peroxide (H 2 O 2 ) in response to soluble stimuli (Kaufmann et al 2009). These works seemingly indicate that the action of microgravity has enhanced the immune response of PMNs, which is inconsistent with the reduced capability of lymphocytes (Cogoli and Tschopp 1985;Konstantinova et al 1993;Meshkov and Rykova 1995;Mills et al 2002;Mills et al 2008Mills et al , 2013, monocytes (Kaur et al 2005(Kaur et al , 2008Crucian et al 2011), NK cells (Rykova et al 1992;Konstantinova et al 1993Konstantinova et al , 1995Mehta et al 2001), and macrophages (Armstrong et al 1995;Hsieh et al 2005;Ortega et al 2012;Adrian et al 2013;Wang et al 2014Wang et al , 2015Brungs et al 2015;Paulsen et al 2015) under microgravity. The underlying mechanisms for such the difference remain unclear.…”
Section: Introductionmentioning
confidence: 97%
“…Reports of monocyte levels associated with spacefl ight have varied ( 24 , 27 , 36 ); however, the percentage of CD14 1 CD16 1 ' proinfl ammatory ' monocytes was reported to decease following spacefl ight ( 10 ). Monocyte surface density of CD14 was found to be decreased postfl ight, whereas the expression of Toll-like receptor 4 was found to be increased ( 21 ). Kaur et al investigated monocyte functional parameters immediately following shortduration spacefl ight and found that oxidative burst and phagocytic capacity were altered, as well as percentages of monocytes capable of being stimulated to produce cytokines ( 20 , 21 ).…”
mentioning
confidence: 92%